Gravity and the behavior of unicellular organisms - Häder, Donat-Peter.; Hemmersbach, Ruth, 1958-; Lebert, Michael, 1959- (New York, NY : Cambridge University Press, 2005)
How do single cells know where is up and down? What is their ecological benefit? How can they be used to study the mechanisms of gravity perception? Historical and current approaches are summarised in order to answer these basic questions of interest to biologists as well as space and gravitational scientists.
Cover; Half-title; Series-title; Title; Copyright; Contents; List of Abbreviations; Preface; 1 Introduction; 1.1 Historical background; 1.2 Definitions; 1.3 Ecological signi.cance; 2 Methods in Gravitational Biology; 2.1 Horizontal microscopes and clinostats; 2.2 Free-fall machine; 2.3 Drop facilities: towers, shafts, and balloons; 2.4 Parabolic .ights; 2.5 Centrifuges; 2.6 Shuttles, satellites, and space stations; 2.7 Direct manipulation of gravisensors; 3 Image Analysis; 3.1 Introduction; 3.2 Hardware; 3.3 Software; 3.4 Fluorescence imaging; 4 Ciliates; 4.1 Paramecium; 4.2 Loxodes.
Includes bibliographical references (pages 205-250) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Gravity -- Physiological effect; Unicellular organisms; Gravité -- Effets physiologiques; Unicellulaires; SCIENCE -- Life Sciences -- Biophysics; Gravity -- Physiological effect; Unicellular organisms; Electronic books; Electronic books